(untitled) (Research, Society and Development, 2021)
Buriti (Mauritia flexuosa L.) is a palm of the Arecaceae family, which occurs in Cerrado, being found notably in the paths. Buriti fruit stands out for having a complex chemical composition, with na emphasis on its lipid fraction. However, depending of the region where the fruits occur, this vegetable oil may have different characteristics. In this sense, this work aimed to characterize the buriti oil from three municipalities in northern region of Minas Gerais. Physical-chemical characterization analyzes were performed, fatty acid profile by gas chromatografy, lutein, α- and β- carotenes by high performance liquid chromatography and total carotenoids by spectrophotometry. The results showed that there was no significant difference between the samples from each region analyzed. Besides, the oil presented good yield, excellent physical-chemical quality, in addition to being a rich source of unsaturated fatty acids and total carotenoids. Thus, buriti oil from the northern region of Minas Gerais has good potential for application by the food industry.